Evaluation of Various Biological Activities of Endemic Sideritis libanotica Extracts - Mehmet ATAS; Nuraniye ERUYGUR; Fazli SOZMEN; Mustafa ERGUL; Merve ERGUL; Huseyin Askin AKPULAT; Esra UCAR (Notulae Scientia Biologicae, 2019)
In recent years, using of plants to develop combine therapies for treatment of certain diseases such as cancer, Alzheimer's disease, and diabetes mellitus is extremely plausible approach. Perhaps, the definitive treatment of some of these diseases is hidden in the complex content of a plant in nature. Thus, in the present study, we decided to determine the biological activities of methanol and water extracts of the endemic Sideritis libanotica. To the best of our knowledge, the present study is the first investigation on antioxidant, enzyme inhibitory activity, antimicrobial activity, and in vitro cytotoxicity of S. libanotica. According to results, while the methanol extract shows better anti-cholinesterase, α-glucosidase, and α-amylase inhibition activity and cytotoxicity than the water extract, the tyrosinase inhibitory activity of the water extract was found to be better than the methanol extract. This study provides valuable information on how the biological activity of endemic S. libanotica changes in different solvent extractions such as water and methanol.